2020
DOI: 10.3389/fgene.2020.00005
|View full text |Cite
|
Sign up to set email alerts
|

Pathogenic Gene Prediction Algorithm Based on Heterogeneous Information Fusion

Abstract: Complex diseases seriously affect people's physical and mental health. The discovery of disease-causing genes has become a target of research. With the emergence of bioinformatics and the rapid development of biotechnology, to overcome the inherent difficulties of the long experimental period and high cost of traditional biomedical methods, researchers have proposed many gene prioritization algorithms that use a large amount of biological data to mine pathogenic genes. However, because the currently known gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 69 publications
0
1
0
Order By: Relevance
“…With the advent of genomewide molecular diagnostic techniques, identifying the underlying genetic defects has been widely used to classify diseases, predict disease progression and determine effective treatment options. [9][10][11][12] Some studies [13][14][15] indicated that mutations in different genes could affect the same cell signalling pathway and result in comparable clinical phenotypes; this finding has helped us understand genomic similarities and the difference between closely related clinical disorders. Accordingly, we hypothesised that paediatric patients who present immune-related conditions with suspected genetic aetiologies might possess monogenic mutations and might share biological mechanisms involving diseaseassociated genes from the same or related pathways.…”
Section: Introductionmentioning
confidence: 99%
“…With the advent of genomewide molecular diagnostic techniques, identifying the underlying genetic defects has been widely used to classify diseases, predict disease progression and determine effective treatment options. [9][10][11][12] Some studies [13][14][15] indicated that mutations in different genes could affect the same cell signalling pathway and result in comparable clinical phenotypes; this finding has helped us understand genomic similarities and the difference between closely related clinical disorders. Accordingly, we hypothesised that paediatric patients who present immune-related conditions with suspected genetic aetiologies might possess monogenic mutations and might share biological mechanisms involving diseaseassociated genes from the same or related pathways.…”
Section: Introductionmentioning
confidence: 99%